KONSEP PENGENDALI LAMPU PENERANGAN RUMAH DARI JARAK JAUH MENGGUNAKAN GELOMBANG FREKUENSI - Danang Danang; Siswanto Siswanto (Elkom : Jurnal Elektronika dan Komputer, 2019)
The Advancement of Science and Technology (Science and Technology) has been widely felt by the general public. Many people enjoy facilities or tools that can simplify and speed up their work. The advancement of science and technology covers various fields, including electronics, automotive machinery, medicine and others. Progress in the electronics sector is growing very rapidly. For example, now many electronic devices are used by the public, such as radio, television, fans and others. The advancement in the electronics field is increasingly sophisticated and modern. For example television, in ancient times we had to press the buttons that were attached to the television, to move the television waves, adjust the volume, and use other adjustment buttons. But now no longer, we can control or regulate the functions that exist on the television from where we sit using the remote control. In modern times like today remote control devices need to be developed so that we can control things from where we sit or from whatever we want, so that human work becomes easier and faster.